Handball coaches` perceptions about the value of working competences according to their coaching background - Mesquita, I.; Borges, M.; Rosado, A.; de Souza, A. (Journal of Sports Science & Medicine, 2011)
The purpose of this study was to analyze the value attributed to given working competences, by Portuguese handball coaches according to their coaching background, certification level, coaching experience, and level of education. A sample of 207 handball coaches responded to a questionnaire which included demographic characteristics and a scale focused on perceptions of the level of importance attributed to working competences. Data analysis included an exploratory factorial analysis applying Maximum Likelihood Factoring (MLF) and Oblimin rotation. These factors were submitted to a One-way ANOVA and Tukey's post hoc multiple comparisons to analyse coaches' perceptions according to their coaching background. A six factor solution was found where three major domains of competences were highlighted; the first one related to training and competition (e.g. planning and conducting the training, team administration in competition, annual and multi-annual planning, and coaching methodology); the second one related to social and cultural issues and management (e.g. implementation of youth sport development projects, team leadership and coach education) and the third one related to the cognitive background (meta-cognitive competences). The importance ascribed to some working competences was influenced by their coaching experience and certification level. Highly experienced and qualified coaches perceived competences of everyday practice, social, cultural and management issues related to training and competition as more important than the other coaches. This study suggests the need to consider some working competences, until now not explicitly present in the Portuguese coaching education curriculum which could enable coaches to choose the best way to practice/work in a manner that will foster and support their professional development.